Mass and composition of rails (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article provides information about rails, which are the main element of the railway. Here we will talk about the mass and their composition, depending on the type of rails.